Detection Of Adulterated Non-Halal Fat (Lard) In Animal Fats Using Gc-Fid,Hplc,Dsc And Ftir Spectroscopy Evaluated With Chemometric Techniques - Dahimi Omar (Universiti Sains Islam Malaysia, 2024)
3090105